Penerapan Komunikasi Terapeutik Perawat dalam Meningkatkan Kepuasan Pasien di Ruang Rawat Inap - Musdalifah, Musdalifah; Pannyiwi, Rahmat; Rahim, Abdul (Barongko: Jurnal Ilmu Kesehatan, 2025)
Therapeutic communication is a crucial component in the implementation of nursing care, aiming to foster a trusting relationship between nurses and patients. Effective implementation of therapeutic communication in inpatient wards is believed to improve patient understanding of their health condition, reduce anxiety, and create a more positive care experience. This study aims to determine the level of nurses' implementation of therapeutic communication and analyze its impact on patient satisfaction in inpatient wards. The study design used a quantitative descriptive approach with accidental sampling technique, involving 80 patients as respondents. The research instrument was a questionnaire that assessed three aspects of therapeutic communication (orientation, working, and termination phases) and patient satisfaction levels. The results showed that nurses' implementation of therapeutic communication was in the good category (73.7%), while patient satisfaction was in the high category (70%). Correlation analysis confirmed a significant positive relationship between therapeutic communication and patient satisfaction. These findings indicate that therapeutic communication plays a crucial role in improving the quality of nursing care, necessitating ongoing training for nurses to maintain and develop effective communication skills.